(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
Diphtheria remains a significant public health concern in many developing countries, particularly in regions characterized by low immunization coverage and undiagnosed infections. One of the major challenges in controlling the disease is the often overlooked contribution of asymptomatic individuals, who may silently sustain and propagate transmission within the population. This study develops a deterministic diphtheria vaccine–treatment model to describe the transmission dynamics of diphtheria within the Nigerian population and to evaluate the impact of different vaccination and treatment strategies on disease prevention and control. Model parameters were estimated using reported diphtheria incidence data obtained from the Nigeria Centre for Disease Control covering the period from 1 December 2022 to 31 July 2023. The basic reproduction number, (R0), was derived analytically, and the estimated mean value of (R0 = 6.010) indicates sustained endemic transmission and suggests that existing intervention strategies are insufficient to effectively curtail disease spread. Sensitivity analysis identified key epidemiological parameters driving diphtheria transmission dynamics, including the recruitment rate, waning immunity rate from fully vaccinated individuals to the susceptible class, asymptomatic transmission rate, and waning immunity rate from partially vaccinated individuals to susceptibles. The findings underscore the critical need for comprehensive control strategies that extend beyond symptomatic case management. Such strategies should include sustained immunization campaigns, booster vaccination programmes, enhanced surveillance, and targeted interventions aimed at reducing asymptomatic transmission. The proposed model provides valuable quantitative insights for evidence-based diphtheria prevention and control policies, particularly in resource-constrained settings.